Factor Vill level given by continuous infusion compared to by bolus in children with hemophilia A undergoing circumcision (case series) - Ridwan Sugiarto, Ridwan Sugiarto T (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: hemophilia is the most common hereditary bleeding disorder in children, and can createÂ challenges in the treatment of complicated bleeding episode. Circumcision and other surgical procedures in persons with hemophilia require anticipatory management plan to prevent and treat bleeding prior to, during and following surgery. Prolonged bleeding can be managed by supplement therapy with Factor VIII, administered intravenously by either bolus (BI) or continuous infusion (CI) to achieve hemostatic plasma Factor VIII levels.Objectives: the aim of this study was to compare plasma activity level of factor VIII in relation to the method of intravenous administration.Methods: commencing 4 days post circumcision, five sequential measurements of plasma Factor VIII levels were done at 6 hourly intervals in 4 boys with hemophilia A who received intravenous Factor Vill, either by 81 or Cl.Result: four patients given continuous infusion showed lower level of Factor VIII compared to bolus therapy. Conclusion: bolus therapy has more increased level of Factor VIII compared to continuous infusion. Bleeding was not found in both therapies (Cl or BI).Â Key words: AHF - continuous infusion - bolus - plasma level